Perjalanan Sejarah Gedung Kesenian Jakarta - Rachmayanti, Sri (Bina Nusantara University, 2010)
The purpose of this study was to examine several aspects that affected the development history of Gedung Kesenian Jakarta, in terms of function, space program and building design. Another thing is to obtain complete data and analyze the development of GKJ based on the historical period. This study will described in terms of history and different functions of building since period of British occupation in Batavia, the arrival of the Dutch until the present era. Besides, it will review the phenomenon of changes in building related to ecology, environment, and current technology equipments. This research is based on data literartures and interviews with the GKJ. In conclusion, this study will discuss the existence of GKJ in relation to local identity, supporting factors of the changes, development and the existence of current GKJ conditions.